Evaluating the effect of temperature on biodiesel production from castor oil (2010)
Problems arising between biofuels and food as raw materials have led to investigating the use of inedible raw materials for their production. This work was aimed at studying the effect of temperature on converting castor oil in biodiesel production. Oil transesterification with methanol was carried out using an alkaline catalyst (0.5% NaOH - water solution) for 1 hour using a 6:1 alcohol/oil molar ratio, at atmospheric pressure and taking temperature as a free variable. The temperature was evaluated at 68°F, 86°F, 104°F and 122ºF. The reaction products were analyzed by gas chromatography (CG-FID) for quantifying the fatty acid methyl esters (FAME) present. The results showed different dispersion depending on temperature, finding that 122°F resulted in less dispersion than the others. CG-FID analysis showed that most FAME content was reached at 122ºF, such temperature giving the highest ricinoleic acid conversion rate. Gas chromatography also revealed that reaction time was adequate, in process conditions, for obtaining ricinoleic acid-based 94.26% con- version.